Penafsiran Hukum Futuristik pada Putusan Mahkamah Konstitusi Nomor 29,51,55/PUU-XXI/2023 - Junaidi, Wulan Novianti (Manabia: Journal of Constitutional Law, 2024)
This research discusses the legal interpretation contained in the Constitutional Court decision Number 29,51,55/PUU-XXI/2023 concerning the age limit for presidential candidates and vice presidential candidates who will run for office in the 2024 general election, who must be at least 40 (forty) Years or have/are currently holding positions elected through general elections including regional head elections in presidential and vice presidential elections. Based on the provisions of article 169 letter (q) of Law Number 7 of 2017 concerning general elections, these provisions are contrary to the 1945 Constitution of the Republic of Indonesia and could cause the loss of citizens' constitutional rights. This research aims to explain the legal interpretation by Constitutional Court judges in the Constitutional Court Decision Number 29,51,55/PUU-XXI/2023 which uses a type of normative juridical research that uses library materials as the main data to analyze cases and analyzes using analytical methods. prescriptive by describing the structure of decisions using logic and legal reasoning, and carried out using interpretation techniques. The results of this research show that the legal interpretation carried out by judges in deciding the Constitutional Court Decision Number 29,51,55/PUU-XXI/2023 uses a futuristic interpretation. Anticipatory in nature, namely an explanation of a law that does not yet have legal force. Thus, to anticipate the loss of constitutional rights, the Constitutional Court should grant the petition of the applicants who will nominate themselves as presidential candidates and vice presidential candidates in the 2024 general election. The legal consequences of using futuristic interpretation methods have the impact of creating potential conflicts of interest and their impact on the general election process.